Defective Interfering Genomes and the Full-Length Viral Genome Trigger RIG-I After Infection With Vesicular Stomatitis Virus in a Replication Dependent Manner - Linder, Andreas; Bothe, Viktoria; Linder, Nicolas; Schwarzlmueller, Paul; Dahlström, Frank; Bartenhagen, Christoph; Dugas, Martin; Pandey, Dharmendra; Thorn-Seshold, Julia; Boehmer, Daniel F. R.; Koenig, Lars M.; Kobold, Sebastian; et al. (Frontiers in Immunology, 2021)
Replication competent vesicular stomatitis virus (VSV) is the basis of a vaccine against Ebola and VSV strains are developed as oncolytic viruses. Both functions depend on the ability of VSV to induce adequate amounts of interferon-α/β. It is therefore important to understand how VSV triggers interferon responses. VSV activates innate immunity via retinoic acid-inducible gene I (RIG-I), a sensor for viral RNA. Our results show that VSV needs to replicate for a robust interferon response. Analysis of RIG-I-associated RNA identified a copy-back defective-interfering (DI) genome and full-length viral genomes as main trigger of RIG-I. VSV stocks depleted of DI genomes lost most of their interferon-stimulating activity. The remaining full-length genome and leader-N-read-through sequences, however, still triggered RIG-I. Awareness for DI genomes as trigger of innate immune responses will help to standardize DI genome content and to purposefully deplete or use DI genomes as natural adjuvants in VSV-based therapeutics.